Review on 3D-printed powder metallurgy alloys with tailored corrosion resistance and surface properties for advanced technology applications - Mahale, Rayappa Shrinivas; Patil, Adarsh; Goggi, Krishnamurthy Prahlad; Raibole, Vaibhav Sanjay; Kakkamari, Prashant P.; Rajendrachari, Shashanka (American Institute of Physics, 2024)
The relentless pursuit of advanced technological solutions demands materials that offer exceptional performance across a spectrum of stringent requirements. This study presents a cutting-edge approach to material design, integrating 3D printing techniques with powder metallurgy to create alloys with bespoke corrosion resistance and surface properties. Our research not only demonstrates the feasibility of this novel approach but also unveils a profound potential for its application in a wide range of advanced technology sectors. Utilizing state-of-the-art 3D printing technology, we engineer complex alloy structures at the micro- and nanoscale, enabling precise control over alloy composition and microstructure. This unprecedented level of customization empowers us to tailor corrosion resistance with pinpoint accuracy, ensuring the materials' longevity and reliability in harsh operational environments. The synergistic combination of powder metallurgy and 3D printing delivers alloys with multifaceted surface properties, including enhanced wear resistance, reduced friction, and improved thermal management. This breakthrough heralds a new era in the development of materials for advanced technology, with potential applications spanning aerospace, automotive, electronics, and more. This study encapsulates a comprehensive examination of these innovative alloys, encompassing material characterization, electrochemical analysis, and mechanical testing. The results reveal promising outcomes, underscoring the immense potential of this approach for optimizing materials in a manner that was previously unattainable. This study stands as a testament to the inexhaustible possibilities at the intersection of materials science, additive manufacturing, and advanced technology. The alloys developed through this method have the potential to revolutionize the performance, durability, and functionality of materials in numerous applications, further advancing our capabilities in an ever-evolving technological landscape. © 2024 Elsevier B.V., All rights reserved.
2023 5th International Conference on Recent Advances in Materials and Manufacturing, ICRAMM 2023 -- Hybrid, Erode -- 203981
Keywords: [No Keywords]